Cross-Linguistic Influences of Learning German in Finnish and German Upper Secondary Schools - Esa M. Penttinen; Heiner Böttger (Journal of Linguistics and Language Teaching)
The aim of this study is to find out what importance upper secondary school learners of German attach to the cross-linguistic influence (CLI) regarding specific aspects of German language learning in Finland and Germany. Cross-linguistic learning gives learners additional skills to learn and understand structures and words in their mother tongue, a second language or a foreign language. The Finnish students (n=100) participating in our survey spoke Finnish as their mother tongue and studied German as a foreign language. German students spoke German either as their mother tongue (n=40) or as a second language (n=60), but they studied German as a native language. The survey data consisted of students' answers to one identical question that they were asked in the school years 2017-2020: 'How does the knowledge of the languages studied at school (Swedish, English, French, Spanish, Latin – cross-linguistic learning) affect their learning of German?' Our research methods were both quantitative and qualitative.